Mid-infrared laser absorption sensor for simultaneous trace detection of CH3CN, H2O, and CH4 in the ambient air - Guan, Hongfei; Wang, Xiaoyu; Liu, Xu; Yuan, Liming; Li, Jinyi; Du, Zhenhui (Sensors and actuators. A. Physical., 2023)
Acetonitrile (CH3CN), a toxic volatile organic compound (VOC), has been widely employed as an important tracer for research of atmospheric transport processes and climate changes. In order to continuously monitor or remote sense ultra-low concentration of CH3CN in the ambient air, we developed a mid-infrared laser absorption sensor for simultaneous detection of CH3CN and ambient H2O and CH4 at the atmospheric window of 3.3 µm. The sensor operated at the fundamental absorption v5-band of CH3CN using wavelength modulation spectroscopy with a distributed feedback interband cascade laser. A multispectrum nonlinear fitting algorithm was developed to deconvolute CH3CN absorption with atmospheric absorption of H2O and CH4. The sensor achieved not only high sensitivity and selectivity detection of CH3CN but also detection of H2O and CH4 as well. The detection limits for CH3CN is 160 ppt, correspond to absorbance as low as 2.3 × 10−7, which is 3 orders of magnitude lower than atmospheric background absorption (10−4 level). The size and weight of the sensor are as low as 32 × 24 × 20 cm and 2.6 kg, respectively. The sensor has the advantages of low measurement uncertainties of less than 1.8 % and good response linearity of 0.999. The technique is expected to be practically feasible for detection of many other VOCs applications. [Display omitted] •Simultaneous trace detection of atmospheric acetonitrile, water, and methane.•Broadband fundamental absorption sensing by an interband cascade laser.•Acetonitrile detection limit 160 ppt corresponding absorbance as low as 2.3 × 10−7.•Highly sensitive and selective sensing below atmospheric absorption background.